2022
DOI: 10.1371/journal.pone.0269977
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for HCV transmission in HIV-positive men who have sex with men in México

Abstract: Purpose In the last two decades transmission of hepatitis C virus (HCV) in HIV positive men who have sex with men (MSM) has been reported globally. Chemsex and specific sexual practices have been identified as risk factors. Our study aimed to identify risk factors for HCV transmission in MSM living with HIV attending in Mexico. Methods We conducted a case-control study from April to December 2019 at the Hospital de Infectología “La Raza” National Medical Center, in Mexico City. A case was defined as an HIV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Vanhommerig et al identified independent associations between HCV acquisition and factors such as sharing sex toys, unprotected fisting, sharing straws for drug use, mucosal disruption (ulcerative STIs) and receptive condomless anal intercourse in HIV‐diagnosed MSM in the Netherlands [15]. Mata‐Marín et al found similar associations in a study of HIV‐diagnosed MSM from Mexico, including sharing straws during cocaine use, sharing sex toys and chemsex [8]. Huang et al in Taiwan linked HCV viraemia among HIV‐positive MSM to recreational drug use, group sex and condomless receptive anal intercourse [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanhommerig et al identified independent associations between HCV acquisition and factors such as sharing sex toys, unprotected fisting, sharing straws for drug use, mucosal disruption (ulcerative STIs) and receptive condomless anal intercourse in HIV‐diagnosed MSM in the Netherlands [15]. Mata‐Marín et al found similar associations in a study of HIV‐diagnosed MSM from Mexico, including sharing straws during cocaine use, sharing sex toys and chemsex [8]. Huang et al in Taiwan linked HCV viraemia among HIV‐positive MSM to recreational drug use, group sex and condomless receptive anal intercourse [25].…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that among MSM, a combination of shared drug utensils, rectal mucosal trauma from receptive anal intercourse, ulcerative sexually transmitted infections (STIs), rectal douching [8,9] and contamination of shared fomites (dildos, condoms, gloves, lubricant, and, more broadly, penises and fists) can indirectly transmit HCV from one person's traumatized rectal mucosa to another's [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual transmission is also a recognized risk factor. Vertical transmission from infected mother to child is also possible [ 1 , 2 , 3 , 7 ]. In 2019, hepatitis C resulted in an estimated 12,696 deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Chemsex engagement involves psychotropic drug use to enhance sexual experiences [ 4 , 5 ] and the subculture of “slamsex” involves intravenous drug injection—both often influenced by sensation‐seeking behaviours [ 6 , 7 ] and pose increased risks of bloodborne virus transmission [ 8 ]. Common substances used in chemsex include crystal methamphetamine (“shabu” in the Philippines) and gamma hydroxybutyrate [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%